2019
DOI: 10.1007/s13187-019-01526-1
|View full text |Cite
|
Sign up to set email alerts
|

Student Exposure to Cancer Patients: an Analysis of Clinical Logbooks and Focus Groups in Clinical Year Medical Students

Abstract: (2019). Student exposure to cancer patients: an analysis of clinical logbooks and focus groups in clinical year medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…15 Certainly previous work on logbooks have demonstrated that the students' actual clinical experience in paediatrics 23 and other fields may be at odds with the prescribed curriculum. 8,16,22,[24][25][26][27] This information can be used by teachers to help work on processes to fill such gaps. 11,22,23,25,28 The active learning nature of the logbook is critical.…”
Section: Perspectives Of the Medical Educators Jenny Mcdonald And Stementioning
confidence: 99%
See 1 more Smart Citation
“…15 Certainly previous work on logbooks have demonstrated that the students' actual clinical experience in paediatrics 23 and other fields may be at odds with the prescribed curriculum. 8,16,22,[24][25][26][27] This information can be used by teachers to help work on processes to fill such gaps. 11,22,23,25,28 The active learning nature of the logbook is critical.…”
Section: Perspectives Of the Medical Educators Jenny Mcdonald And Stementioning
confidence: 99%
“…No point making the goal impossible to reach 22 and certainly ongoing evaluation of logbooks is recommended 15 . Certainly previous work on logbooks have demonstrated that the students' actual clinical experience in paediatrics 23 and other fields may be at odds with the prescribed curriculum 8,16,22,24–27 . This information can be used by teachers to help work on processes to fill such gaps 11,22,23,25,28 …”
Section: Perspectives Of the Medical Educatorsmentioning
confidence: 99%
“…Whilst cancer is the leading cause of death in Australia [3], increased survivorship places significant demands on the health system [4]. Studies highlight that Australian medical students are ill-prepared to care for cancer patients upon graduation [5][6][7][8]. Additionally, medical students and junior doctors have questioned the quality of their own cancer education [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies highlight that Australian medical students are ill-prepared to care for cancer patients upon graduation [5][6][7][8]. Additionally, medical students and junior doctors have questioned the quality of their own cancer education [8][9][10][11][12]. The lack of a national medical curriculum results in considerable diversity in cancer teaching and clinical exposure between schools [5,13].…”
Section: Introductionmentioning
confidence: 99%
“…Logbooks positively influence students' learning by providing a clear picture of what they have accomplished during their learning experiences [12]. This is argued to add structure and organization and help bridge gaps in the apprenticeship model of clinical teaching that was often 'unstructured and opportunistic' [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%